Gender performativity in Butoh: gender subversion by Nyoba Kan in Malaysia - Lim, Siew Ling (Tanjong Malim, 2015)
Gender performativity in Butoh: gender subversion by Nyoba Kan in Malaysia by Lim, Siew Ling